Conference Record of the 1991 IEEE Industry Applications Society Annual Meeting
DOI: 10.1109/ias.1991.178318
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-current characteristics of plate type precipitator geometry under combined DC/pulse energizations

Abstract: An attempt has been made to study the voltage-current characteristics of a wire-plate precipitator geometry under clean air conditions. Helical wires have been used as corona electrodes. The studies were conducted with DC and DC superposed on nanosecond pulse respectively. The repetitive pulses with a rise time of the order of nanoseconds were generated from a MARX type impulse voltage generator. A comparative study of effect of pulse repetition rate, pulse width and effect of DC bias has been made on the volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The study also shows that a t 50 pulses per second, the current density increases exponentially with increase in pulse voltage as compared to that at lower repetition rates. A further insight into these results are presented by the author in [20][21][22]. In the present work, the studies were carried out with a pulse repetition rate of 50, at which good electrical characteristics were obtained.…”
Section: Experimental Studiesmentioning
confidence: 70%
“…The study also shows that a t 50 pulses per second, the current density increases exponentially with increase in pulse voltage as compared to that at lower repetition rates. A further insight into these results are presented by the author in [20][21][22]. In the present work, the studies were carried out with a pulse repetition rate of 50, at which good electrical characteristics were obtained.…”
Section: Experimental Studiesmentioning
confidence: 70%
“…Cristina and Feliziani [19] proposed a procedure for the numerical computation of the electric field and current density distributions in a dc electrostatic precipitator in the presence of dust, taking into account the particle-size distribution. The performance of WDEP s under impulse voltages has been investigated by many researchers [20][21][22][23][24][25][26]. It has been reported that the application of a pulse energization to electrostatic precipitators has substantial benefits when high resistivity particulate materials are involved.…”
Section: Electrode Misalignment Induced Malfunctionsmentioning
confidence: 99%
“…Assuming known particle charge density values, (21) is integrated and assuming known ionic charge density, (21) is integrated. The integration of (21) and (22) is repeated iteratively in order to obtain the ionic and particle space charge density values at the nodes located along the axis of the flux tube. The iterative procedure stops when the ionic and particle charge densities calculated at the FE node in two successive iterations are less than a pre-specified error, 1 δ (taken as …”
Section: B Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation